2016
DOI: 10.1093/ckj/sfw009
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of chronic kidney disease in a semi-urban population of Western India

Abstract: BackgroundGlobally there is an increase in incidence of chronic kidney diseases (CKDs). Diabetes mellitus (DM), hypertension and stone diseases are the major risk factors for CKD. We organized kidney disease screening camps in a semi-urban population of Gujarat, India on the occasion of World Kidney Day (WKD).MethodsVoluntary participants from six towns were screened. Estimated glomerular filtration rate (eGFR) was calculated by the Modification of Diet in Renal Disease formula and CKD was defined as an eGFR <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 27 publications
1
20
1
Order By: Relevance
“…Hypertension, diabetes mellitus, and abdominal obesity are the traditional risk factors for CKD in India as shown in previous studies [ 3 , 18 , 19 ]. However, none of these were associated with CKD in the present study.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Hypertension, diabetes mellitus, and abdominal obesity are the traditional risk factors for CKD in India as shown in previous studies [ 3 , 18 , 19 ]. However, none of these were associated with CKD in the present study.…”
Section: Discussionmentioning
confidence: 84%
“…However, prevalence estimates from other studies are based on smaller sample sizes, and registry estimates could be overestimated due to potential high reporting bias from an area that is already known to have high CKD prevalence. The coastal region of Saurashtra and non-coastal region of North Gujarat had CKD prevalence of 15.7% and 26%, respectively [ 19 ]. A recent population-based survey of Delhi and Chennai showed that the age standardized prevalence of CKD is 8.7% [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the 16 studies included in our systematic review, nine were of high quality [ 17 , 18 , 20 , 21 , 25 , 26 , 28 , 30 , 31 ] and seven were of moderate quality [ 19 , 22 24 , 27 , 29 , 32 ] based on the preselected criteria described in ‘Quality appraisal’ section. Detail of the study quality is illustrated in Additional file 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Trivedi H et al found in kidney disease screening camps in a semi-urban population of Gujarat, India CKD was 20.93% and eGFR <60 mL/min/1.73 m 2 was noted in 8.29% (participants with known diabetes, stone diseases, hypertension, kidney/liver/cardiac disease, hepatitis, HIV, transplant recipients, pregnant women and those <18 years were excluded from this study). 4 This study brings to light the underdetermined burden of CKD in India.…”
Section: Introductionmentioning
confidence: 93%